The striking cabbies of Cairo and other stories : crafts and guilds in Egypt, 1863-1914 - Chalcraft, John T., 1970- (SUNY series in the social and economic history of the Middle East., 2004)
This book charts new directions in Egyptian social history, providing the first systematic account of adaptation and protest among crafts and service workers in Egypt in the nineteenth and early twentieth centuries. Using a wealth of new sources, John T. Chalcraft challenges conventional notions of craft stagnation and decline by recovering the largely unknown histories of crafts workers' restructuring in the face of world economic integration, and their petitions, demonstrations, and strike-action at a time of state-building and colonial rule. Chalcraft demonstrates the economic importance of petty producers and service providers, and tells the story of widespread collective assertion couched in new discourses of citizenship and nationalism. He also gives a new interpretation of the end of the guilds in Egypt and addresses larger debates about unevenness under capitalism. Book jacket.